Law Enforcement as a Systematic Effort to Preserve the Environment - Shena Novera Hulaifa (CV. Rayyan Dwi Bharata, 2023)
The purpose of this research is to know and analyze Law Enforcement as a Systematic Effort to Preserve the Environment. The research method that I used to complete this article is a normative research method. The data collection method prioritizes legal research with various legal materials through the results of a review of written sources such as documents, books, journals, which are related to legal materials because they are different from the ambiguity of law enforcement in environmental issues. The results of the study say that the legal action given to the perpetrators of environmental pollution and destruction consists of administrative aspects, civil aspects, and criminal aspects. Article 76 (2) Environmental Protection and Management Law No. 32 of 2009 stated that administrative sanctions consist of written warnings, enforcement by the government, freezing of environmental permits and revocation of environmental permits. Regarding the settlement of environmental disputes according to Article 84 of Law no. 32 of 2009, there are two ways to claim compensation and/or environmental cleaning costs, namely environmental dispute resolution outside the court and environmental dispute settlement outside the court